Computational fluid dynamics analysis of seven selected hydrofoils for different angle of attack - Puteri Nurfarah Adawiyah Taslin,; Aliashim Albani,; Mohd Zamri Ibrahim,; Mohd Azlan Musa,; Zulkifli Mohd Yusop,; Mohd Afifi Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper aims to conduct a Computational fluid dynamics (CFD) analysis of seven selected hydrofoils at different angles of attack (AOA) for application in ocean current energy converter blades. The hydrofoil models are NACA0012, NACA0015, NACA2412, NACA2414, NACA2415, NACA 4412, and E387. The geometry was managed using the Design Modeler tool. The fluid flow simulation was carried out using ANSYS Fluent. The result showed the performance of E387 is better than other hydrofoils as it gives better lift force with the least drag force, resulting in better hydrodynamics of turbine blade. Overall, the value of lift and drag coefficients at 10o was more consistent than 0o and 20o AOA.